2012
DOI: 10.1111/j.1651-2227.2011.02556.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in care and short‐term outcome for very preterm infants in Estonia

Abstract: The outcome for very preterm infants in Estonia has improved since 2002. With proactive perinatal management and less invasive neonatal care, survival until discharge increased without concomitant increases in neonatal morbidity and the length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Between 2002 and 2012, infant mortality rates decreased from 28% to 11% but despite these efforts, Romania still faces high perinatal and neonatal mortalities, particularly in comparison to Western European countries . A comparison between published international results (Table ) shows that there are considerable differences in mortality rates between different countries worldwide . As in other Eastern European countries, this topic has not been well studied in Romania due to a lack of available data.…”
Section: Mortality Rates Of Very Preterm Infants In Various Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Between 2002 and 2012, infant mortality rates decreased from 28% to 11% but despite these efforts, Romania still faces high perinatal and neonatal mortalities, particularly in comparison to Western European countries . A comparison between published international results (Table ) shows that there are considerable differences in mortality rates between different countries worldwide . As in other Eastern European countries, this topic has not been well studied in Romania due to a lack of available data.…”
Section: Mortality Rates Of Very Preterm Infants In Various Countriesmentioning
confidence: 99%
“…4 A comparison between published international results (Table 1) shows that there are considerable differences in mortality rates between different countries worldwide. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] As in other Eastern European countries, this topic has not been well studied in Romania due to a lack of available data. Up-to-date estimates of infant survival after extreme prematurity are important for assessing perinatal care centers and for clinical guidelines and parental counseling.…”
mentioning
confidence: 99%
“…A recent nationwide study showed that, since 2002, survival of VLGA infants until discharge has improved in Estonia. This occurred without a concomitant increase in neonatal morbidity, which nonetheless remained relatively high . The present population‐based follow‐up study evaluated the outcomes of VLGA infants born in 2007 at 2 years of corrected age, to benchmark the quality of care in perinatal services in Estonia.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge for perinatal services in Estonia is to decrease long‐term disability in very preterm infants without compromising their survival. Given that the rate of very preterm live births in Estonia is within the range of other European countries , and that improvement of the socio‐environmental milieu requires time, there is an urgent need for a reduction in neonatal morbidity to improve the long‐term outlook for VLGA infants. Consequently, the main requirements in Estonia to improve the outcome of such infants are the ongoing implementation of evidence‐based practice, reorganization of perinatal care by establishing perinatal centres that offer tertiary level intensive care on site and ongoing surveillance of iatrogenic factors that might have detrimental effects on the health of VLGA infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation